Judge Manfred Lachs and Judicial Law-Making : Opinions on the International Court of Justice, 1967-1993 - McWhinney, Edward, (Human Rights and Humanitarian Law - Book Archive pre-2000., 1995)
This volume, the second in the series The Judges , which collects and synthesizes the opinions of leading international contemporary judges who have contributed significantly to the progressive development of international law, is devoted to the work of Judge Manfred Lachs, who was elected to the International Court of Justice in 1967. In his Foreword to the study, UN Secretary General Boutros Boutros-Ghali says of Lachs that ` His contribution to jurisprudence is especially noteworthy. He initiated a significant part of the jurisprudence of the Court in the area of human rights. He contributed to the formulation of the right to self-determination, helped to develop the law of the sea, and participated in the work of the Court in many other areas. But, above all, he was at the forefront of the most progressive battles of the Court, demonstrating great personal courage and great analytical rigour. As President of the Court, he showed a constant interest in improving its procedures and developing relations between the judicial organ and other organs of the United Nations. ' Edward McWhinney's masterly essay, which precedes extracts from Manfred Lachs' Opinions and from some Judgements in which he played a crucial role, is essential reading for all those interested in the World Court, as well for Manfred Lachs' countless admirers, students and colleagues. See Less